Antibacterial And Antifungal Effect Of Some Natural Extracts And Their Potential Use As Photosensitizers - Al-fawwaz, Abdullah T.; Al-Khaza’leh, Khaled A. (European Scientific Journal, ESJ, 2016)
One of the threats on the health sector is the appearance of multi antibiotic resistant microorganisms. Thus, this occurs because of using natural and synthetic antimicrobial agents in excessive doses. Now, many scientists all around the world are performing research on natural extracts that have antimicrobial activity using photodynamic therapy (PDT) which involves light activation. The aim of this study, however, is to evaluate the effect of photodynamic antimicrobial chemotherapy using extracts from Pomegranate (Punica granatum), Cinnamon (Cinnamomum verum), Roselle (Hibiscus sabdariffa), Carob (Ceratonia siliqua), and Nigella or black cumin oil (Nigella sativa) against two gram-positive and two gram-negative bacteria (Bacillus cereus, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa) respectively; and three different fungi (Aspergillus niger, Mucor sp., and Rhizopus sp.), using agar well diffusion method. The prepared methanolic extracts presented absorption between 300 and –900 nm wavelengths. The maximum activity of Roselle (Hibiscus sabdariffa) was against Staphylococcus aureus in total darkness with 52.5 ± 2.5 mm inhibition zone diameter. Also, the most sensitive fungi was Mucor sp. Cinnamon (Cinnamomum verum) extract was with 31.0 ± 1.0 mm inhibition zone diameters. The results showed that there was an inhibitory effect of Cinnamon (Cinnamomum verum) and Roselle (Hibiscus sabdariffa) extracts against most of the tested species.